2011
DOI: 10.1080/08905436.2011.547113
|View full text |Cite
|
Sign up to set email alerts
|

Biological Availability and Preliminary Selenium Speciation in Selenium-Enriched Mycelium ofLentinula edodes (Berk.)

Abstract: Our goal is to obtain a new food supplement -a chemopreventive preparation derived from selenium (Se)-enriched Lentinula edodes mycelium. In the present study the bioavailability of selenium from Se-enriched mycelium preparations was tested in vitro and in vivo. Three different preparations of selenated mycelium were compared: dried mycelium, lyophilized mycelium, and lyophilized-autolyzed mycelium. In vitro, estimated Se bioavailabilities were 60%, 82%, and 98%, respectively. In vivo bioavailability was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Supplementation of Se can be necessary because nutritional Se deficiency affects 500–1,000 million people worldwide, especially those from the Keshan disease area of China ( Combs, 2001 ). The availability and biological activity of Se depend on its dose and chemical form ( Turło et al, 2011 ). In trace amounts, Se confers antioxidant capacities to a number of selenoproteins ( Izquierdo, Casas & Herrero, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementation of Se can be necessary because nutritional Se deficiency affects 500–1,000 million people worldwide, especially those from the Keshan disease area of China ( Combs, 2001 ). The availability and biological activity of Se depend on its dose and chemical form ( Turło et al, 2011 ). In trace amounts, Se confers antioxidant capacities to a number of selenoproteins ( Izquierdo, Casas & Herrero, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of mushrooms are Se-poor, a considerable amount of organic Se can accumulate in mushrooms supplied with selenite or other forms of Se ( Falandysz, 2008 ). Turło et al (2011) reported that the mycelium of Lentinula edodes cultured in selenite-fortified substrate accumulated Se in organic compounds, and the synergetic effect of Se compounds and active polysaccharides gave it a strong chemopreventive activity.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of Se can be necessary, because nutritional Se deficiency affects 500-1000 million people worldwide, especially those from the Keshan disease area of China (Combs 2001). The availability and biological activity of Se depend on its dose and chemical form (Turło et al 2011). In trace amount, Se confers antioxidant capacities to a number of selenoproteins (Izquierdo et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional Se deficiency affects 500-1000 million people worldwide, especially those from the Keshan disease area of China, and Se supplementation can be necessary for them (Combs 2001). The availability and biological activity of Se depend on its dose and chemical form (Turło et al 2011). In trace amount, Se confers antioxidant capacities to a number of selenoproteins (Izquierdo et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of mushrooms are Se-poor, a considerable amount of organic Se can accumulate in mushrooms supplied with selenite or other forms of Se (Falandysz 2008). Turło et al (2011) reported that the mycelium of Lentinula edodes cultured in Se-fortified substrate accumulated Se in organic compounds, and the synergetic effect of Se compounds and active polysaccharides gave it a strong chemopreventive activity.…”
Section: Introductionmentioning
confidence: 99%